2016
DOI: 10.1111/dme.13080
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for managing diabetes in Ramadan

Abstract: Up to date guidelines for the management of treatment regimes are set-out for those with Type 1 and Type 2 diabetes who wish to fast during Ramadan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
64
1
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(72 citation statements)
references
References 38 publications
(60 reference statements)
0
64
1
5
Order By: Relevance
“…2,9 The Diabetes and Ramadan International Alliance (DAR) have published guidelines which provide clear guidance for health professionals and patients on the safety of fasting and changes in medication recommended for patients planning to fast. 1 The guidance states that patients at very high risk or high risk should be discouraged from fasting but that, if they insist, they should receive structured education and careful monitoring by the diabetes specialist team, monitor blood glucose regularly, adjust medication as per recommendations and be prepared to stop the fast if hypoglycaemia (glucose <3.9 mmol/L) or hyperglycaemia (glucose >16.7 mmol/L) occurs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,9 The Diabetes and Ramadan International Alliance (DAR) have published guidelines which provide clear guidance for health professionals and patients on the safety of fasting and changes in medication recommended for patients planning to fast. 1 The guidance states that patients at very high risk or high risk should be discouraged from fasting but that, if they insist, they should receive structured education and careful monitoring by the diabetes specialist team, monitor blood glucose regularly, adjust medication as per recommendations and be prepared to stop the fast if hypoglycaemia (glucose <3.9 mmol/L) or hyperglycaemia (glucose >16.7 mmol/L) occurs.…”
Section: Discussionmentioning
confidence: 99%
“…1 A number of guidelines exist to enable health professionals to advise Muslim patients on their risk of fasting, and how to manage their diet and diabetes medication whilst fasting. 1,2 Previous studies have looked at outcomes of fasting in patients predominantly in tropical climates where the duration of fasting is generally stable at around 12-14 hours. 3,4 In this study, we aimed to survey Muslim patients with diabetes in East London on their experience of fasting during summer 2016, a period when the duration of fasting was over 19 hours.…”
Section: Introductionmentioning
confidence: 99%
“…Type 2 diabetes mellitus is one of the most frequently encountered metabolic syndromes worldwide. The most recent meta‐analysis showed that the overall prevalence (9.1%) has been increasing among inland residents in China since the 1970s, and it increased rapidly with age.…”
Section: Introductionmentioning
confidence: 99%
“…Ramadan occurred during the second period (between M 3 and M 6 ) and may have interfered with glycaemic control because of modifications in nutritional habits 13. However, the period between inclusion and M 3 was chosen so that there was no interference with the primary end point.…”
Section: Discussionmentioning
confidence: 99%